Analysis of attraction and distribution of attracted resources of international financial institutions - Sultonmurodov Bobir Bakhodirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Commercial banks, like other subjects of economic relations, must have a certain amount of money, i.e. resources, to ensure their commercial and economic activities. The resources of commercial banks are necessary active elements of banking activity. A commercial bank, on the one hand, attracts free funds of legal entities and individuals, thereby forming a resource base, and on the other hand, places it on its own behalf at its own risk on the terms of repayment, urgency, and payment. According to the method of formation, all the resources of a commercial bank are divided into their own and borrowed (attracted). The main source of resources of commercial banks are attracted funds, which make up about 70-80% of all banking resources.